(untitled) (World Bulletin of Public Health, 2024)
No specific changes are observed in fetal liver in COVID-19. Most directly related, damage to the endothelium of liver blood vessels, dystrophic changes occurring in the endothelium of the walls of hem capillary sinusoids, mucoid thickening, multifocal desquamation and plug-like obturation of small capillary sinusoids, as well as dystrophic changes in the hepatocytes close to this field: fatty dystrophy, with changes in the appearance of hydropic dystrophy continues. Clinically, morphologically, depending on the area occupied by most of these changes, it continues with the occurrence of liver failure and HELP syndrome. From a clinical morphological point of view, the development of parenchymatous jaundice and progressive necrosis of the liver was studied. Macroscopically, it is determined that the liver is enlarged, softened, its outer surface has a variegated color, that is, small foci of hemorrhages and yellow-brown foci appear under the membrane, and its parenchyma also has a false nutmeg color when the tissue is cut.